StarTrack: A Framework for Enabling Track-Based Applications - Ananthanarayanan, Ganesh; Haridasan, Maya; Mohomed, Iqbal; Terry, Doug; Thekkath, Chandramohan A. (ACM MobiSys, 2009)
Mobile devices are increasingly equipped with hardware and software services allowing them to determine their locations, but support for building location-aware applications remains rudimentary. This paper proposes tracks of location coordinates as a high-level abstraction for a new class of mobile applications including ride sharing, location-based collaboration, and health monitoring. Each track is a sequence of entries recording a person’s time, location, and application specific data. StarTrack provides applications with a comprehensive set of operations for recording, comparing, clustering and querying tracks. StarTrack can efficiently operate on thousands of tracks.